Synthesis and evaluation of thiomannosides, potent and orally active FimH inhibitors. Issue 17 (15th September 2018) - Sattigeri, Jitendra A.; Garg, Malvika; Bhateja, Pragya; Soni, Ajay; Rauf, Abdul Rehman Abdul; Gupta, Mahendrakumar; Deshmukh, Mahesh S.; Jain, Tarun; Alekar, Nidhi; Barman, Tarani Kanta; Jha, Paras; Chaira, Tridib; et al.
Graphical abstract: Highlights: SARs of thiomannoside derivatives as FimH inhibitor. FimH inhibitory activity and potential to inhibit biofilm formation. Prophylactic effect in urinary tract infection model in mice. Abstract: FimH is a type I fimbrial lectin located at the tip of type-1 pili of Gram-negative uropathogenic Escherichia coli (UPEC) guiding its ability to adhere and infect urothelial cells. Accordingly, blocking FimH with small molecule inhibitor is considered as a promising new therapeutic alternative to treat urinary tract infections caused by UPEC. Herein, we report that compounds having the S -glycosidic bond (thiomannosides) had improved metabolic stability and plasma exposures when dosed orally. Especially compound 5h showed the potential to inhibit biofilm formation and also to disrupt the preformed biofilm. And compound 5h showed prophylactic effect in UTI model in mice.